Stop and go, where is my flow? How and when daily aversive morning commutes are negatively related to employees' motivational states and behavior at work. - Rivkin, Wladislaw (My University, 2021)
Despite convincing evidence about the general negative consequences of commuting for individuals and societies, our understanding of how aversive commutes are linked to employees' effectiveness at work is limited. Drawing on theories of self-regulation and by extension a conservation of resources perspective, we develop a framework that explains how an aversive morning commute-a resource-depleting experience characterized by interruptions of automated travel behaviors-impairs employees' immersion in uninterrupted work (i.e., flow), which in turn reduces employee effectiveness (i.e., work engagement, subjective performance, and OCB-I). We further delineate theoretical arguments for daily self-control demands as a boundary condition that amplifies this relation and propose the satisfaction of employees' basic needs as protective factors. Two diary studies across 10 workdays each (Study 1: 53 employees, 411 day-level data points; Study 2: 91 employees, 719 day-level data points) support most of our hypotheses. Study 1 demonstrates that daily aversive morning commutes negatively affect employees' daily work engagement through lower levels of flow experiences, but only on days with high impulse control demands. In addition, we find initial support that employees' general autonomy and competence needs satisfaction attenuate this interaction. Study 2 rules out alternative mechanisms (negative affect and tension), demonstrates ego depletion as an additional mediator of the relation between aversive morning commutes and work effectiveness, and replicates the hypothesized three-way interaction for daily competence need satisfaction. We critically discuss the findings and reflect on corporate interventions, which may allow people to more easily flow to and at work.
PUBLISHED
Keywords: Employee effectiveness; Commuting; Conservation of resources; Flow experience; Self-regulatory resources